Description of two new species of Sycorax Curtis (Diptera, Psychodidae, Sycoracinae) from the Atlantic Rain Forest of Espírito Santo, Brazil - Santos, Claudiney Biral dos; Bravo, Freddy (Biota Neotropica, 2009)
Two new species of Sycorax Curtis from the Atlantic Rain Forest of Espírito Santo, S. cariacicaensis Santos & Bravo sp. nov. and S. espiritosantensis Santos & Bravo sp. nov., are described and illustrated.